Social Isolation Alters Social and Mating Behavior in the R451C Neuroligin Mouse Model of Autism. (31st January 2017) - Burrows, E. L.; Eastwood, A. F.; May, C.; Kolbe, S. C.; Hill, T.; McLachlan, N. M.; Churilov, L.; Hannan, A. J.
Abstract : Autism spectrum disorder (ASD) is a neurodevelopmental disorder typified by impaired social communication and restrictive and repetitive behaviors. Mice serve as an ideal candidate organism for studying the neural mechanisms that subserve these symptoms. The Neuroligin-3 (NL3) mouse, expressing a R451C mutation discovered in two Swedish brothers with ASD, exhibits impaired social interactions and heightened aggressive behavior towards male mice. Social interactions with female mice have not been characterized and in the present study were assessed in male N L 3 R 451 C and WT mice. Mice were housed in social and isolation conditions to test for isolation-induced increases in social interaction. Tests were repeated to investigate potential differences in interaction in naïve and experienced mice. We identified heightened interest in mating and atypical aggressive behavior in N L 3 R 451 C mice. N L 3 R 451 C mice exhibited normal social interaction with WT females, indicating that abnormal aggressive behavior towards females is not due to altered motivation to engage. Social isolation rearing heightened interest in social behavior in all mice. Isolation housing selectively modulated the response to female pheromones in N L 3 R 451 C mice. This study is the first to show altered mating behavior in the N L 3 R 451 C mouse and has provided new insights into the aggressive phenotype in this model.